APPLICATION OF THE FLOUR MIXTURE IN THE OATED LIVER RECIPE - N. L. Naumova; I. M. Chanov; M. V. Syrvacheva (Современная наука и инновации, 2022)
A study was made of the quality and nutritional value of oatmeal cookies based on dry flour mix. The recipe, chemical composition, microstructure, mineral value of the raw materials used, quality indicators and nutritional value of the finished product were studied.